Treatment related severe and fatal adverse events with cetuximab in colorectal cancer patients: a meta-analysis. (1st June 2013) - Zhang, Di; Ye, Junjie; Xu, Tangpeng; Xiong, Bin
Abstract : Purpose: Cetuximab has been approved by FDA for the treatment of advanced/metastatic colorectal cancer. Whether cetuximab treatment is associated with an increase of severe adverse events in colorectal cancer (CRC) patients remains a question. The purpose is to assess the risk of severe adverse events of cetuximab treatment in advanced/metastatic CRC patients. Patients and methods: Search of EMBASE, PubMed, and ScienceDirect between 1 January, 2000 and 1 July 2012 for relevant randomized control trials (RCTs). Previous meta-analyses related with cetuximab treatment were also identified for eligible RCTs. Eligible studies were RCTs of advanced/metastatic CRC patients assigned to cetuximab or control group. Data were extracted by two authors for severe and fatal adverse events. Results: Nine RCTs, involving 8520 patients with CRC were included. Using a fixed-effects model, the proportion of patients with severe adverse events was higher in the cetuximab group than in control group with Mantel-Haenszel methods (OR, 2·19; 95% CI, 1·99-2·41; incidence, 70·0% versus 51·2%; P <0·001). The most common severe adverse events were neutropenia, diarrhea, and rash. However, cetuximab was not associated with increased risk of fatal adverse events (OR, 1·41; 95% CI, 0·99-2·03; incidence, 1·8% versus. 1·3%). Conclusion: In this meta-analysis of RCTs, cetuximab was associated with an increased risk of severe adverse events. There is no evidence of an increased risk of fatal adverse events with cetuximab.